Comparative insights into Fusobacterium nucleatum and Helicobacter pylori in human cancers - Gusmaulemova, Alua; Kurentay, Botakoz; Bayanbek, Dina; Kulmambetova, Gulmira (Frontiers in Microbiology, 2025)
Fusobacterium nucleatum and Helicobacter pylori are two microbial species increasingly recognized for their roles in gastrointestinal (GI) carcinogenesis, particularly in colorectal cancer (CRC) and gastric cancer (GC), respectively. While H. pylori has been long classified as a Group 1 carcinogen due to its well-characterized pathogenic mechanisms, F. nucleatum has more recently emerged as a key microbial contributor to CRC, with growing evidence linking it to tumor progression, immune evasion, and poor clinical outcomes. Despite occupying anatomically distinct niches within the GI tract, both bacteria converge on similar oncogenic pathways, including the activation of NF-κB signaling, β-catenin pathway dysregulation, and epithelial barrier disruption. In parallel, dietary factors – particularly the consumption of red and processed meats – contribute additional oncogenic pressure via carcinogenic compounds such as heme iron, N-nitroso compounds, and polycyclic aromatic hydrocarbons. These dietary components not only damage host tissue but may also potentiate bacterial virulence and promote microbial persistence. This review provides a comparative analysis of the oncogenic strategies employed by F. nucleatum and H. pylori, with an emphasis on their interactions with diet-derived carcinogens and implications for therapeutic interventions targeting the microbiota–diet–host axis in GI cancers.